2021
DOI: 10.1155/2021/7589756
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Particle Swarm Optimization Algorithm Ensemble Model Applied to Classification of Unbalanced Data

Abstract: Unbalanced data classification is a major challenge in the field of data mining. Random forest, as an ensemble learning method, is usually used to solve the problem of unbalanced data classification. For the existing random forest-based classification prediction model, its hyperparameters are dependent on empirical settings, which leads to the problem of unsatisfactory model performance. In order to make random forest find the optimum modelling corresponding to the character of unbalanced data sets and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…The investigation [11] found that population diversity and inertia weight are the keys to avoid premature convergence of PSO; the core guiding principles of the algorithm are clustering and adaptive adjustment of inertia weight. Through fast search clustering methods, the population can be adaptively divided into several subgroups to better explore the solution space of the problem.…”
Section: Adaptive Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…The investigation [11] found that population diversity and inertia weight are the keys to avoid premature convergence of PSO; the core guiding principles of the algorithm are clustering and adaptive adjustment of inertia weight. Through fast search clustering methods, the population can be adaptively divided into several subgroups to better explore the solution space of the problem.…”
Section: Adaptive Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…PSO merupakan algoritma Optimasi fitur dapat meningkatkan nilai akurasi yang dihasilkan PSO telah digunakan untuk optimasi peningkatan akurasi untuk Random forest, decision tree, naïve bayes dan KKN untuk klasifikasi dataset diabetes [15]. PSO dapat dikombinasikan dengan Teknik data sampling untuk meningkatkan akurasi dari algoritma an ensemble Classifier dalam klasifikasi [16]. Penelitian ini focus dan memberikan kotribusi keterbaruan diantaranya: membuat model klasifikasi kepuasaan layanan public menggunakan an ensemble classifier, menguji pengaruh pemilihan fitur terhadapat klasifikasi ensemble classifier, menguji pengaruh feature selection terhadap algoritma an ensemble classifier dan yang terakhir adalah kombinasi Teknik data sampling dan pemilihan fitur terhadap kinerja algoritma Ensemble classifier Dari latar belakang permasalahan dan studi literatur pada penelitian terdahulu, maka tujuan penelitian ini adalah untuk deteksi malware menggunakan algoritma supervised learning yaitu Random Forest (RF), XGBOOST, catboost dan lightgbm, yang sebelumnya akan dilakukan selection feature untuk meningkatkan nilai akurasi, sehingga model yang dihasilkan dapat direkomendasikan untuk deteksi malware.…”
Section: Latar Belakangunclassified
“…For example, Irsoy et al [ 11 ] applied RNN for text sentiment orientation classification, Kim et al [ 12 ] used CNN for text sentiment orientation classification, and Soni et al [ 14 ] proposed TextConvoNet, a novel convolutional neural network (CNN)-based architecture for solving binary and multi-class text classification problems. At the same time, some scholars have begun to study the classification problem based on imbalanced data [ 15 , 16 ]. For example, Yin Hao et al [ 17 ] proposed a resampling multi-channel model, which randomly sampled the imbalanced samples to make the number of samples balanced before training.…”
Section: Introductionmentioning
confidence: 99%